Gambaran Asupan Serat, Kolesterol dan Kejadian Hipertensi Pada Lansia Di Kelurahan Peguyangan Kecamatan Denpasar Utara - Ni_Wayan Novia Febrian_Rahayu; I_Made Rodja Suantara; Hertog Nursanyoto (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Hypertension is often nicknamed "Silent Killer". The elderly are most vulnerable to hypertension. Hypertension is triggered by various factors, one of which is less fiber intake and excessive cholesterol intake. This study aims to determine the description of fiber intake, cholesterol and the hypertension incidence of elderly in Peguyangan village, North Denpasar District. This type of research is Observational with Cross Sectional approach with a total sample of 59 people. The results obtained were 28.8% suffering from hypertension, including 76.5% with fiber intake in the less category, 23.5% with enough category and elderly with cholesterol intake obtained 82.4% at risk of cholesterol intake, 5.8% of normal cholesterol intake, and 11.8% of cholesterol is not at risk. The results of this study indicate a tendency for distribution patterns between fiber intake, cholesterol and the incidence of hypertension in the elderly. Intake in the elderly has an important role in the treatment of hypertension. Especially in fiber and cholesterol intake. If enough fiber intake and not excessive cholesterol intake can reduce the risk of hypertension in the elderly. Keywords: Fiber Intake, Cholesterol Intake, Hypertension, Elderly